COVID-19 vaccine uptake in mental healthcare users: Czech nationwide register study - Pisl, Vojtech; Vevera, Jan (Vaccine, 2023)
BACKGROUND: The excessive covid-related mortality of psychiatric patients was reduced by vaccination. The vaccine uptake in patients diagnosed with different mental health disorders is, however, not fully described. AIMS: A nationwide, record-based retrospective cross-sectional study examines the effect of substance use, psychotic, affective, anxiety, and personality disorders on COVID-19 vaccination rates in August and December 2021. Further, it quantifies the effect of receiving mental healthcare on vaccine uptake. METHODS: The COVID-19 vaccine rates of mental healthcare users in August and December 2021 were examined using logistic regression models adjusted for sex and age on a sample of 7,235,690 adult inhabitants of the Czech Republic. The probability of vaccine uptake in the week following mental healthcare appointment or hospitalization on any day in the fall 2021 was compared to the general probability of getting vaccinated during that week. RESULTS: The vaccination rate in August 2021 was related to history of hospitalization due to substance use (OR = 0.71), personality (OR = 0.87), psychotic (OR = 0.92), and anxiety (OR = 1.15) disorders, while mood disorders had no effect (OR = 1.00). Compared to general population, mental healthcare users were undervaccinated in August but not in December 2021. Vaccine uptake was low in those with history of psychiatric hospitalizations but higher in those utilizing inpatient or outpatient mental healthcare recently, predominantly for affective disorders. Increased vaccine uptake was observed following utilization of mental healthcare as well as in those with repeated psychiatric hospitalizations. CONCLUSIONS: The vaccination rates of mental healthcare users relative to general population largely differ across nosological categories and during the vaccination campaign. Psychiatrists were successful in promoting vaccination against COVID-19.
Keywords: Cross-Sectional Studies; Adult; Retrospective Studies; průřezové studie; Vaccination; Czech Republic; retrospektivní studie; služby péče o duševní zdraví; dospělí; Mental Health Services; COVID-19; Česká republika; Humans; lidé; vakcinace; vakcíny proti COVID-19; COVID-19 Vaccines